2018
DOI: 10.1177/2051415818776186
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and satisfaction with transcutaneous electrostimulation of the posterior tibial nerve in overactive bladder syndrome

Abstract: Objective: Overactive bladder is a disease with a high prevalence. The management is difficult, because different demographic, social or economic aspects converge. Our objective was to evaluate the efficacy and satisfaction in patients with overactive bladder treated with transcutaneous electrostimulation of the posterior tibial nerve. Methods: This was a prospective and descriptive study of 45 patients with overactive bladder (with or without detrusor overactivity) resistant to pharmacological treatment. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Finally, 19 studies [ 3 , 4 , 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included. Of these, nine were experimental [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], including eight RTCs [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 24 ] ( Table 2 ); four were observational studies [ 5 , 25 , 26 , 27 ] ( Table 3 ), and six were either systematic reviews [ 4 , 29 , 31 ] or a meta-analysis [ 28 ], while two encompassed both types of studies [ 30 , 32 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 19 studies [ 3 , 4 , 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included. Of these, nine were experimental [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], including eight RTCs [ 3 , 17 , 18 , 19 , 20 , 21 , 22 , 24 ] ( Table 2 ); four were observational studies [ 5 , 25 , 26 , 27 ] ( Table 3 ), and six were either systematic reviews [ 4 , 29 , 31 ] or a meta-analysis [ 28 ], while two encompassed both types of studies [ 30 , 32 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the additional complications to those observed in the analysis of results [ 3 , 19 , 21 , 23 , 26 , 28 , 30 , 32 ] were urinary tract infections in 10/17 studies (peer comparisons revealed that OnabotulinumtoxinA was associated with a greater incidence of urine infections vs. placebo, sacral neurostimulation (SNS), and PTNS); ranking in order of fewest infections: first PTNS, second SNS, third placebo, and fourth OnabotulinumtoxinA. Further, urine retention with a need for intermittent catheterization was found in 11/17, with peer comparisons showing that OnabotulinumtoxinA was associated with a greater incidence of retention vs. placebo, SNS, and PTNS; ranking in order of lowest incidence: first SNM, second placebo, third PTNS, and fourth OnabotulinumtoxinA [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation